Insurance Regulation in Jordan: New Rules — Old System - Vittas, Dimitri (World Bank, Washington, D.C., 2013)
The Jordanian insurance market has been free from extensive state ownership and pervasive premium, product, investment, and reinsurance controls. However, these positive features have been marred by the licensing of a large number of private companies, often on political rather than professional criteria, and the resulting fragmentation of the sector. Various policies have perpetuated the fragmentation of the sector, while regulatory forbearance has allowed the continuing operation of several weak companies. Despite the avoidance of pervasive controls and extensive state ownership, and the presence of a large number of private companies, the insurance industry is not well developed. This mainly reflects the underdevelopment of life insurance. In contrast, the level of general insurance is comparable to several other developing countries in the region and elsewhere. A major modernization effort has been undertaken in recent years. This has included the enactment of a new insurance law and the creation of a new Insurance Commission. The latter has made considerable progress in expanding its staff, undertaking a wide-ranging training program to upgrade skills, and implementing a multi-year action plan aimed at modernizing the regulatory framework and enhancing the efficiency of the sector.